Phenological growth stages of biquinho pepper according to the BBCH scale - Paula Andriessa Krause; Marcelo Dotto; Kelli Pirola; Elouize Xavier; Camila Moreno Giarola; Allan Remor Lopes (Acta Scientiarum. Biological Sciences, 2023)
Biquinho pepper has been gaining prominence on the national scene because of its sweet taste and low pungency. Therefore, this study aimed to describe the phenological growth stages of biquinho pepper according to the BBCH scale. Based on this general scale, biquinho pepper showed 9 of the 10 principal stages (germination, leaf development, formation of side shoots, shoot development, development of the harvestable vegetative parts of the plant, flowering, fruit development, coloring or ripening of fruits and senescence). In addition, 25 secondary growth stages have also been described. The study will act as a tool for adoption of better crop management practices (nutrient management, irrigation scheduling, monitoring of management of pests and timely harvest of fruits).